Peranan Pemerintah Desa Dalam Penyaluran Bantuan Pangan Non Tunai pada Masa Pandemi Covid-19 di Desa Simpang Empat Kecamatan Bebesen Kabupaten Aceh Tengah - Reza Eka Saputra; Beby Masitho Batubara; Agung Suharyanto (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2022)
The Non-Cash Food Assistance Program (BPNT) is an assistance that is distributed non-cash from the government to Beneficiary Families (KPM) each month in the amount of Rp. 110,000/KPM through an electronic account mechanism in the form of a Prosperous Family Card (KKS) which aims to improve economic conditions. family. The purpose of this study was to find out how the role of the village government in the distribution of Non-Cash Food Assistance (BPNT) in Simpang Empat Village, Bebesen District, Central Aceh Regency and to find out what factors became obstacles in the distribution of the Non-Cash Food Assistance (BPNT) program in the village. Simpang Empat Bebesen District, Central Aceh Regency. The method used by researchers in this study is a descriptive qualitative research method. The results of this study indicate that the distribution of the Non-Cash Food Assistance (BPNT) program in Simpang Empat Village, Bebesen District, Central Aceh Regency has not gone well, this is because the population administration is still incomplete.